Recombinant fragilysin isoforms cause E-cadherin cleavage of intact cells and do not cleave isolated E-cadherin. (June 2015) - Kharlampieva, Daria; Manuvera, Valentin; Podgorny, Oleg; Grafskaia, Ekaterina; Kovalchuk, Sergey; Pobeguts, Olga; Altukhov, Ilya; Govorun, Vadim; Lazarev, Vassili
Abstract: The fragilysin (BFT) is a protein secreted by enterotoxigenic Bacteroides fragilis strains. BFT contains zinc-binding motif which was found in the metzincins family of metalloproteinases. In this study, we generated three known recombinant isoforms of BFT using Escherichia coli, tested their activity and examined whether E-cadherin is a substrate for BFTs. BFT treatment of HT-29 cells induced endogenous E-cadherin cleavage, and this BFT activity requires the native structure of zinc-binding motif. At the same time recombinant BFTs did not cleave recombinant E-cadherin or E-cadherin in isolated cell fractions. It indicates that E-cadherin may be not direct substrate for BFT. We also detected and identified proteins released into the cultural medium after HT-29 cells treatment with BFT. The role of these proteins in pathogenesis and cell response to BFT remains to be determined. Highlights: Recombinant wild-type BFT isoforms have similar biological activities. None of BFT isoforms cleave E-cadherin isolated from various sources. The native zinc-binding motif of BFT is necessary for E-cadherin release from cells. BFT like ADAM family proteases causes the release of membrane proteins.